Comparison of sustainable life cycle assessment on building construction methods: IBS versus conventional - Nik Mazlan Nik Muhammad Akif; Ismail Sushilawati; Saryanto Hendi; Wan Nasaruddin Wan Anwar Faiz; Tukiat Ikhwan Shah Tisadi (BIO Web of Conferences)
Industrial Building Systems (IBS) is prominently known as one of the sustainable construction options. However, some construction practitioners still doubt the sustainability of this method, which may be due to their lack of awareness and knowledge. Furthermore, the construction industry, particularly in Malaysia, does not yet have precise and reliable figures demonstrating the amount of carbon footprint reduction attributable to the usage of IBS. Therefore, this study aims to evaluate the IBS building sustainability performance based on carbon emission values. A life cycle assessment (LCA) comparison between conventional methods and the IBS method will be conducted to see the carbon footprint percentage based on comparing these two methods. In the end, LCA will consider every single flow and relate the activity when analyzing the sustainability issues of the building. Materials, energy, and product waste throughout the life cycle will be identified so that the environmental impact can be determined from before the design and manufacturing phase starts until the completion of the construction activities. This study is expected to prove the sustainability of the IBS method compared to the conventional methods to increase the confidence level of construction implementers and further expand the implementation of the IBS method. It is also hoped that the awareness of the sustainability characteristics of IBS construction can change the perception of the construction implementers by starting to think about long-term implications such as GWP when in the phase of decision-making in a construction project development.